166k views
2 votes
Which expression represents the sum of (2x - 5y) and (x + y)?

A. 3x - 4y
B. 3x - 6y
C. x - 4y
D. x- 6y

User Jim Archer
by
5.3k points

2 Answers

5 votes
It would be A. 3x - 4y
This is because 2x + x = 3x, and -5y + y = 4y.
User Uahmed
by
5.2k points
5 votes
You can write the expression into
2x - 5y + x + y

Now classify the same variables, x with x and y with y, then add the parts with the same variable
2x - 5y + x + y
= 2x + x - 5y + y
= 3x - 4y

The answer is a
User DarkLeafyGreen
by
6.2k points